Praziquantel and factor H recruitment differentially affect the susceptibility of Schistosoma mansoni to complement-mediated damage - van Beek, Anna E.; Jeanguenat, Hannah; Häberli, Cécile; Pouw, Richard B.; Lamers, Christina; Pál, Gábor; Gál, Péter; Schmidt, Christoph Q.; Ricklin, Daniel; Keiser, Jennifer (Frontiers in Immunology, 2024)
BackgroundSchistosomes are highly efficient evaders of human immunity, as evident by their ability to survive in human blood for years. How they protect themselves against the constant attack by a key element of innate immunity, the complement system, has remained unclear. In this study, new light is shed on the interaction between distinct life-cycle stages of Schistosoma mansoni and the human complement system.ResultsWe demonstrate that schistosomula, the young stage assumed immediately after cercaria penetration of the skin, are extremely vulnerable towards complement-mediated killing as only 10-20% survive. The survival rate increases to 70% already within 30 minutes and reaches close to 100% within two hours. Pathway-specific complement inhibitors revealed the alternative pathway of complement activation as the main contributor to killing and damage of the schistosomula. Moreover, the complement regulator factor H is recruited by the schistosomula in this early stage to evade killing. Surviving parasites appear fully viable despite the ongoing complement attack, as demonstrated by the deposition of C3 fragments. However, when exposed to the widely used schistocidal drug praziquantel, the vulnerability of 24 h-old schistosomula towards complement-mediated killing is notably increased; no such effect was observed for mefloquine or oxamniquine. Similar to the younger life-cycle stages, adult worms remain under complement attack. C3 fragments were found all over the outer surface (tegument), deposited mostly on the ridges and not on the tubercles.ConclusionThe recruitment of factor H merits more detailed studies that pinpoint the molecules involved and elucidate the novel possibilities to intercept the uncovered immune evasion therapeutically. That praziquantel and complement work in synergy is surprising and may in the future result in enhanced understanding of the drug’s mechanism of action.